Spontaneous intrathyroidal hematoma causing airway obstruction: A case report. Issue 35 (August 2016) - Best, Corliss A.E.; Dhaliwal, Sandeep; Tam, Samantha; Low, T. Hubert; Hughes, Brian; Fung, Kevin; MacNeil, S. Danielle
Abstract: Introduction: Spontaneous thyroid hemorrhage is a rare occurrence that results in pain, discomfort, and occasionally compressive symptoms. Infrequently, extensive thyroid hemorrhage can result in a rapidly expanding hematoma resulting in airway compromise. This is a case of an otherwise healthy young woman, 3 months postpartum, with a slowly expanding spontaneous thyroid hemorrhage that measured at 7 × 5.5 × 5 cm by computed tomography. She ultimately required intubation to manage respiratory distress and subsequently a hemithyroidectomy for definitive treatment. The case presentation is followed by a literature review where known etiologies of thyroid hematoma including traumatic and nontraumatic causes, precipitating anticoagulation, and spontaneous rupture of branches of the external carotid artery are outlined. The potential links to pregnancy are explored. The roles of bedside thyroid ultrasound in the emergency department and lateral neck roentgenogram in diagnosis are explored. The importance of airway management and indications for conservative versus surgical treatments are discussed. Conclusions: This is a case of a spontaneous intrathyroidal hemorrhage, which progressed over days to ultimately cause airway compromise. It is imperative that physicians are educated on the appropriate detection and management of the potentially life-threatening spontaneous thyroid hematoma.